HUBUNGAN WORD OF MOUTH TERHADAP KEPUTUSAN PELANGGAN DI PERCETAKAN AMANI OFFSET SURAKARTA - Buddy Riyanto, Fachmy Anwari, Siswanta & (Transformasi, 2016)
Type of this research is quantitative. The theory is the theory of Kotler (2000) for themeasurement of the variable declared Word Of Mouth is also a marketing strategy to makecustomers talk (to talk), promoting (to promote), and sell (to sell) to other customers. Thepopulation in this research is all customers Amani Offset Surakarta, as for the withdrawal ofsamples done by non probability sampling aksidental so obtained as many as 100 peoplesampling. Premier data obtained through the dissemination of the questionnaire. As for theresults of this research are: based on Product Moment has a significant positive relationshipbetween the Word Of Mouth of customer Word Of Mouth thus capable of affecting the consumerin using the printing products Amani Offset so the more frequent consumers of Surakarta talkabout positive things about a product, then the increase of customers to have that product. Ifconsumers are increasingly talking about negative things about a product, then decreased tocustomer also have a product.Key words: influence of Word Of Mouth, Customer Communication, marketing.